Conversion of the Native 24‐mer Ferritin Nanocage into Its Non‐Native 16‐mer Analogue by Insertion of Extra Amino Acid Residues. (25th November 2016) - Zhang, Shengli; Zang, Jiachen; Wang, Wenming; Chen, Hai; Zhang, Xiaorong; Wang, Fudi; Wang, Hongfei; Zhao, Guanghua
Abstract: Protein assemblies with high symmetry are widely distributed in nature. Most efforts so far have focused on repurposing these protein assemblies, a strategy that is ultimately limited by the structures available. To overcome this limitation, methods for fabricating novel self‐assembling proteins have received intensive interest. Herein, by reengineering the key subunit interfaces of native 24‐mer protein cage with octahedral symmetry through amino acid residues insertion, we fabricated a 16‐mer lenticular nanocage whose structure is unique among all known protein cages. This newly non‐native protein can be used for encapsulation of bioactive compounds and exhibits high uptake efficiency by cancer cells. More importantly, the above strategy could be applied to other naturally occurring protein assemblies with high symmetry, leading to the generation of new proteins with unexplored functions.